2017
DOI: 10.1111/vcp.12517
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of, and influence of hemolysis, lipemia, and icterus on serum lipase activity as measured by the v‐LIP‐P slide

Abstract: These results show that Spec cPL is specific for pancreatic lipase, while the v-LIP-P slide is not. In addition, hemolysis and lipemia had no effect on Spec cPL, while severe icterus resulted in a slight decrease in Spec cPL. Hemolysis and icterus had a significant effect on the v-LIP-P slide. The effect of lipemia on the v-LIP-P slide cannot be conclusively established based on this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Pancreatic lipase immunoreactivity concentrations, as measured using Spec fPL and Spec cPL, are currently considered the most sensitive and specific laboratory tests for feline and canine pancreatitis, depending on the diagnostic criteria of pancreatitis and cutoffs used 12,15,17,34‐37 . Various studies describing the analytical validation of the Spec cPL assay have shown this assay to be precise, linear, stable, reproducible, and unaffected by hemolysis, lipemia, or bilirubinemia 9,38 . In this study, we further showed that extrapancreatic lipases (ie, heparin‐induced lipases, hepatic and lipoprotein lipases) do not interfere with Spec PL measurements.…”
Section: Discussionsupporting
confidence: 58%
“…Pancreatic lipase immunoreactivity concentrations, as measured using Spec fPL and Spec cPL, are currently considered the most sensitive and specific laboratory tests for feline and canine pancreatitis, depending on the diagnostic criteria of pancreatitis and cutoffs used 12,15,17,34‐37 . Various studies describing the analytical validation of the Spec cPL assay have shown this assay to be precise, linear, stable, reproducible, and unaffected by hemolysis, lipemia, or bilirubinemia 9,38 . In this study, we further showed that extrapancreatic lipases (ie, heparin‐induced lipases, hepatic and lipoprotein lipases) do not interfere with Spec PL measurements.…”
Section: Discussionsupporting
confidence: 58%
“…However, overlap existed and 42% of dogs had lipase concentrations above the lower 20% of the reference interval, indicating that many dogs had substantial detection of lipase by the V‐LIP‐P (Fujifilm Corporation) assay. Thus, triolein does not appear to be specific for the measurement of lipase of pancreatic origin 78 …”
Section: Lipase Assaysmentioning
confidence: 96%
“…The standard for such studies uses the addition of Intralipid to serum, which has been reported to falsely amplify the effects of lipids on lipase activity assays. In 8 dogs with naturally‐occurring hyperlipidemia, the effects of lipid on V‐LIP‐P (Fujifilm Corporation) results were lower 78 . This study also evaluated V‐LIP‐P (Fujifilm Corporation) lipase concentrations in 50 dogs with EPI.…”
Section: Lipase Assaysmentioning
confidence: 97%
See 2 more Smart Citations